Malignant brain tumor in early pregnancy mistaken for hyperemesis gravidarum - Naoki Abe; Maki Goto; Sachino Kira; Mariko Matsuno; Sotaro Hayashi; Miho Oda; Lifa Lee; Yoko To; Satoshi Nishiyama; Hiroshi Tsujioka (Taiwanese Journal of Obstetrics & Gynecology)
Objectives: The main objective of this case report is to discuss the differentiation between hyperemesis gravidarum and a brain tumor in the presence of hyperemesis symptoms in the first trimester of pregnancy. Case report: A patient was initially diagnosed with hyperemesis gravidarum in early pregnancy and was hospitalized. After hospitalization, cerebral hemorrhage and cerebral hernia due to convulsions occurred. Magnetic resonance imaging showed a brain tumor. She underwent a craniotomy and then an artificial abortion. Despite treatment with radiation and chemotherapy, she died 9 months later. Conclusion: Differentiating between hyperemesis gravidarum and a brain tumor based on a physical examination alone is difficult. Imaging should be performed when exacerbation of consciousness with suspected intracranial organic disease occurs.